2011
DOI: 10.1111/j.1471-4159.2011.07547.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell adhesion molecules contribute to Alzheimer’s disease: multiple pathway analyses of two genome‐wide association studies

Abstract: Alzheimer's disease (AD) is a kind of highly heritable and complex neurological disorder. AD is also the leading cause of dementia in the elderly (Harold et al. 2009;Hooli and Tanzi 2009). The disorder is characterized by extracellular b-amyloid plaque deposition, intraneuronal tau pathology, neuronalcell death, vascular dysfunction and inflammatory processes (Hochstrasser et al. 2010

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 68 publications
1
53
0
Order By: Relevance
“…Previous Results from Pathway Analysis of AD GWAS Prior to this study, six pathway analyses of AD GWAS have been reported with five studies using the KEGG database [4][5][6][7][8][9]. We compared our findings with the previous pathway analyses of AD GWAS.…”
Section: Two Ad Brain Expression Gwas Datasetsmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous Results from Pathway Analysis of AD GWAS Prior to this study, six pathway analyses of AD GWAS have been reported with five studies using the KEGG database [4][5][6][7][8][9]. We compared our findings with the previous pathway analyses of AD GWAS.…”
Section: Two Ad Brain Expression Gwas Datasetsmentioning
confidence: 97%
“…A large proportion of AD heritability has yet to be explained. Fortunately, the existing large-scale GWAS datasets provide strong support for the investigation of AD mechanisms using pathway analysis methods [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CAMs like N-cadherin (Reiss et al 2005), CD44 (Okamoto et al 2001;Stoeck et al 2006), L-selectin , and NCAM (neural cell adhesion molecule) (Kalus et al 2006), related to neuroinflammation, are confirmed to be substrates shedded by ADAM17. Although there is little direct evidence between EGF or CAM signaling and AD, by using GWAS (genome-wide association studies) datasets and Kyoto Encyclopaedia of Genes and Genomes (KEGG) analysis, there seemed to be potential relevance of CAM pathway to AD pathogenesis (Liu et al 2012) ( Table 2). Neutralization of the inflammation pathway, like TNFa signaling pathway, by blocking the interaction of the cytokine with its cognate receptors, has been demonstrated as a feasible approach to treating inflammatory disease.…”
Section: Adam17 and Ad-related Neuroinflammationmentioning
confidence: 99%
“…Basic and clinical research indicates that CAMs play an important role in mediation of the immune and inflammatory processes of cardiovascular diseases [25]. Genome-wide association studies also suggest that human diseases such as atherosclerosis and Alzheimer's disease are related to the processes of CAMs [26,27]. Intercellular adhesion molecule-1 (ICAM-1), as a member of the immunoglobulin superfamily, plays an important role in mediating leukocyte adhesion and the development of atherogenesis [28].…”
Section: Discussionmentioning
confidence: 99%